Приобретение права собственности на самовольную постройку - Добрынина, Ольга (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The study aims at an evaluation of the acquisition of the ownership of the unauthorised construction. The author present this form of the acquisition of the right to property in the civil code of the Russian Federation emphasising the necessity of fulfilling law norms.